Playing to Win: Improving Support Services for Student Athletes with Learning Disabilities in Institutions of Higher Learning - Kaff, Marilyn S.; Leslie-Toogood, Adrienne; Miller, Teresa L. (My University, 2005)
Although much has been written about the impact of learning disabilities on the performance of students of school age, only recently has the emphasis shifted to students of college age. University services and supports for these students have not kept pace with the dramatic influx of students with special needs, often because instructors and counselors are unfamiliar with their needs and requirements (Lock & Layton, 2001). Student athletes with learning disabilities may experience a multitude of difficulties throughout their academic careers. Academic advisors and faculty need to focus on addressing both the metacognitive and affective needs of student athletes with learning disabilities. The authors propose a combined approach of strategy instruction and self-advocacy which allows student athletes to not only understand their learning needs but to request the supports that will allow them to be more successful learners. This multi-faceted approach can assist students in reaching their potential.
Keywords: at-risk; skills; models